al-Tanāsub al-Qaṣaṣī fī Tafsīr al-Taḥrīr wa-al-Tanwīr: Taḥlīl Qiṣṣat Banī Isrā'īl fī Al-Qur'ān - Habib Abdillah (Al-Zahra : Journal for Islamic and Arabic Studies, 2025)
This study explores narrative coherence in al-Taḥrīr wa al-Tanwīr through an analysis of the Qur’anic accounts of the Children of Israel. It addresses a central problem: how Ibn ‘Āshūr employs ‘ilm al-munāsabah to construct a cohesive narrative unity within these stories. The scope is limited to verses recounting the stories of the Children of Israel in the first half of the Qur’an. Methodologically, it adopts a qualitative analytical-comparative approach, utilizing textual analysis, contextual examination, and comparative exegesis between al-Taḥrīr wa al-Tanwīr and selected classical tafsīr works. Secondary sources were selected for their direct relevance to ‘ilm al-munāsabah and Qur’anic narrative studies. The findings reveal a consistent narrative structure in the stories of the Children of Israel, dispersed across approximately 870 verses in 31 chapters. The study also uncovers Ibn ‘Āshūr’s methodological approach in linking narratives to their surah-level contexts through precise rhetorical, pedagogical, and thematic tools. The results demonstrate the distinctiveness of Ibn ‘Āshūr’s approach compared to classical exegesis in articulating the contextual architecture of Qur’anic stories, making this research a significant contribution to the development of narrative and munāsabah studies in contemporary Qur’anic exegesis.